Designing Decisions in the Unknown: A Generative Model. Issue 2 (14th August 2018) - Le Masson, Pascal; Hatchuel, Armand; Le Glatin, Mario; Weil, Benoit
Abstract : This study examines how design theory enables to extend decision‐making logic to the 'unknown, ' which often appears as the strange territory beyond the rationality of the decision‐maker. We contribute to the foundations of management by making the unknown an actionable notion for the decision‐maker. To this end, we build on the pioneering works in 'managing in the unknown' and on design theory to systematically characterize rational forms of action in the unknown. We show that action consists of designing decisions in the unknown and can be organized on the basis of the notion of a 'decision‐driven design path, ' which is not yet a decision but helps to organize the generation of a better decision‐making situation. Our decision‐design model allows us to identify four archetypes of decision‐driven design paths. They enable us to discuss the variety of known organizational forms that managers can rely on to explore the unknown.